Investigation on partial discharge activities in cross-linked polyethene power cable using finite element analysis. (January 2020) - Isa, M A M; Rohani, M N K H; Rosmi, A S; Isa, M; Rosle, N; Mustafa, W A; Daniel, I N; Roslan, M A
Abstract: The nationwide usage of cross-linked polyethylene (XLPE) for medium to high voltage distribution networks are practically common due to its excellent electrical, thermal and mechanical properties and widely installed through existing network of cable line in Malaysia. However, cable exposures to harsh climates coupled with inadvertent damage throughout installation or transportation are influencing the presence of voids inside the insulation leading to the initiation of partial discharges (PD) in the cable line. Therefore, this study is important to investigate the activities of PD due to the manifestation of voids in XLPE cable and how it affects the physical, electrical and mechanical characteristics of the cable. Analysis has been performed using Finite Element Analysis (FEA) tool to simulate the PD activities in a 2D model of a three (3) core-XLPE insulated armoured sheathed cable (500 mm 2, 11 kV) with several placements of voids. The varied placement and radius of voids is very crucial in order to achieve comprehensive analysis. From the obtained result, it has been established that closest the void to the core yielded higher electric field potential. Additionally, it is verified from the simulation that the larger the size of void, the higher the electric field potential consequently increasing the current density inside the void. This simulation and analysis is quite important to provide better insight pertaining to the behaviour of PD in correspond to the presence of voids which will accelerate ageing failure in insulation framework of the XLPE cable.